Dietary Polyamines and Diseases: Reducing Polyamine Intake Can Be Beneficial in Cancer Treatment - Büyükuslu, Nihal (Journal of Nutrients, 2015)
Polyamines are most abundant polycationic natural amines and involved in several physiological processes. They can be supplied by the endogenous synthesis inside the cell or by the intake from exogenous sources. The polyamine content of cells is regulated by biosynthesis, degradation, uptake and excretion. The benefits of dietary polyamines can be changed; they may be harmful, neutral or beneficial. For example, increasing the amount of dietary polyamines is suggested during rapid growth, such as during the neonatal period, wound healing and after surgery. However, in cancer patients, reducing polyamine dietary intake has been shown to be beneficial on the quality of life. This review aimed to evaluate the effect of dietary polyamines in health and disease.